Mediation's Potential to Reduce Occupational Stress: A New Perspective. (11th May 2015) - Tallodi, Timea
<x xml:space="preserve">Abstract</x> This article is a response to several factors: the emergence of occupational stress as a main theme in a qualitative study involving parties to workplace mediation; the recognition that mediation, being underpinned by psychological stress models, can reduce occupational stress; and a lack of studies investigating mediation's potential to alleviate occupational stress. Linking mediation's main qualities to interactional and transactional models of stress, the article provides a new angle on mediation's dynamics. Findings are illustrated by extracts from interviews. Suggestions are made as to ways in which workplace mediation might be used more proactively in relation to stress.